Henoch-Schönlein syndrome and selective IgA deficiency. Issue 2 (February 1985) - Martini, A; Ravelli, A; Notarangelo, L D; Burgio, V L; Plebani, A
Abstract : A 9 year old girl presented with clinical manifestations of Henoch-Schönlein syndrome and macroscopic haematuria. Laboratory investigations showed selective IgA deficiency and renal biopsy showed mesangial proliferative glomerulonephritis with diffuse granular deposits of C3 on immunofluorescence. IgA deposits were absent.